2010
DOI: 10.1002/jcb.22679
|View full text |Cite
|
Sign up to set email alerts
|

Roles of GRP78 in physiology and cancer

Abstract: As one member of 70 kDa heat shock proteins, glucose-regulated protein 78 (GRP78) participates in protein folding, transportation and degradation. This sort of capacity can be enhanced by stresses under which GRP78 is induced rapidly. Unlike its homologues, GRP78 presents multifaceted subcellular position: When ER retention, it serves as the switch of unfolded protein response; When mitochondrial binding, it directly interacts with apoptotic executors; When cell surface residing, it recognizes extracellular li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 50 publications
(49 reference statements)
2
112
1
3
Order By: Relevance
“…Thus, blocking anti-GRP78 antibodies, small molecule inhibitors, anticancer agent conjugated with vehicle targeted to GRP78, or GRP78 promoter-driven expression of suicide genes may be expected in the treatment of cancers. 12 Vaspin indeed has a beneficial role in ameliorating vascular dysfunction; future studies are required to address the concern that vaspin or its mimetics may promote the tumor growth by acting on the cell surface GRP78 on tumors cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, blocking anti-GRP78 antibodies, small molecule inhibitors, anticancer agent conjugated with vehicle targeted to GRP78, or GRP78 promoter-driven expression of suicide genes may be expected in the treatment of cancers. 12 Vaspin indeed has a beneficial role in ameliorating vascular dysfunction; future studies are required to address the concern that vaspin or its mimetics may promote the tumor growth by acting on the cell surface GRP78 on tumors cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 Beyond the ER retention, GRP78 is also associated with various anchor membrane proteins on the cell surface and functions as a receptor for various ligands and a signaling hub for either in cell survival or cell death. [12][13][14][15] Recently, we demonstrated that vaspin ameliorates ER stress and insulin resistance under obese states by acting as a ligand for cell-surface GRP78/MTJ-1 (murine tumor cell DnaJ-like protein-1) complex in the liver. 16 Here, we show vaspin exerts antiapoptotic potential to the endothelial cells and it protects from the vascular injuries in a balloon-injured model in Wistar rats with streptozotocin-induced diabetes mellitus.…”
mentioning
confidence: 99%
“…CHOP is a transcription factor, the physiological level of which is relatively low; however, the protein expression of CHOP may be strongly induced in response to ERS under diverse pathological conditions (28). Similarly, upregulated expression of GRP78 is often regarded as an indicator of ERS (29).…”
Section: Discussionmentioning
confidence: 99%
“…4B). GRP78 is an ER-localized chaperone protein that is induced by the unfolded protein response in response to ER stress (26,27). Binding of GRP78 to GST-FL-Anks4b and GST-M-Anks4b, but not to GST, GST-N-Anks4b, or C-Anks4b, was confirmed by Western blotting using a specific antibody for GRP78 (Fig.…”
Section: Hnf4␣ and Hnf1␣ Synergistically Activate Transcription Ofmentioning
confidence: 95%